PENERAPAN PENDEKATAN INKUIRI BERBASIS MASALAH ISLAMI UNTUK MENINGKATKAN KEMAMPUAN LITERASI SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Dede Maharani (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Islamic Religious Education (PAI) plays an important role in shaping the character, morals and spirituality of students in Indonesia. However, PAI learning often faces challenges related to students' low literacy levels in understanding Islamic teachings in depth. This research aims to examine the application of an Islamic problem-based inquiry approach in improving students' literacy skills in PAI learning through the literature review method. The results of the study show that this approach is effective in increasing students' understanding of PAI material, developing critical thinking skills, and increasing students' motivation and active participation in learning. The Islamic problem-based inquiry approach is also able to develop students' information literacy skills, which include the ability to search, evaluate and process information from various sources. Additionally, this approach encourages collaboration and the development of social skills through group work and discussions between students. In conclusion, the application of an Islamic problem-based inquiry approach in PAI learning has a significant positive impact on students' literacy abilities. Therefore, this approach can be considered as one of the potential innovative methods for improving the quality of PAI education in Indonesia. Effective implementation requires support and training for teachers, as well as the development of relevant and challenging teaching materials. This research suggests that the application of an Islamic problem-based inquiry approach can be an effective solution for improving students' literacy skills in PAI learning, as well as forming students who are characterful, critical and literate.